Kemampuan Komitmen Organisasi Memoderasi Kompetensi Pejabat Penatausahaan Keuangan dan SPI Pada Kualitas Laporan Keuangan Kota Denpasar - Astika, Ida Bagus Putra; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p12, 2018)
This study examines the quality of financial reporting Denpasar District. The financial statements of Denpasar has three times successively retain unqualified opinion (WTP) of the Supreme Audit Agency (BPK) since 2013 (The government of Denpasar, 2015). The success of Denpasar must be maintained through the improvement, especially in the field of HR, SPI, and the commitment of the region. This study will be conducted in the environment SKPD Denpasar. The research was conducted in 2016. The research scope is limited to the financial administration officials (PPK) as the parties relating to the preparation of financial statements SKPD. Data analysis techniques used in this research is descriptive and inductive statistical analsisi. Analysis Descriptive statistics such as frequency distribution of respondents' answers on statements in the questionnaire. Inductive statistical analysis used in this study is the SEM-PLS. This research proves that the competence of the administration officials keuangandan internal control system affects the quality of financial statements, while the organizational commitment does not affect the quality of financial statements. Organizational commitment not found moderating influence of the financial administration officials competence and internal control system on the quality of financial statements. Keywords: organizational commitment, competence, internal control system, the quality of financial reports, and working units.